Assessing The Contribution Of Tourism To Economic Growth In Nepal - Ojha, Krishna Prasad; Kandel, Madan; Shah, Kapil (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
This study examines the impact of tourism on Nepal’s economic growth using time-series data from 2001 to 2024. Employing linear and multiple regression analyses, results show a significant upward trend in tourist arrivals, increasing by approximately 1,493 visitors annually, and a corresponding rise in tourism’s contribution to GDP by 0.0184 percentage points per year. A strong positive correlation (r = 0.87) between tourist arrivals and GDP contribution underscores tourism’s key role in economic development. Despite a sharp decline in tourism during 2020 due to the COVID-19 pandemic, structural break analysis indicates a resilient recovery in subsequent years. Stationarity tests show that important variables were not stable, so we adjusted the data to make it suitable for accurate time-series modeling. Findings highlight the sustained and growing economic importance of tourism in Nepal and suggest avenues for future research incorporating advanced modeling techniques.